2021
DOI: 10.3847/psj/ac1f9b
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape of (11351) Leucus from Five Occultations

Abstract: We present observations of five stellar occultations for (11351) Leucus and reports from two efforts on (21900) Orus. Both objects are prime mission candidate targets for the Lucy Discovery mission. Combined results for Leucus indicate a very dark surface with p V = 0.037 ± 0.001, which is derived from the average of the multichord occultations. Our estimate of the triaxial ellipsoidal shape is for axial diameters of 63.8 × 36.6 × 29.6 km assuming that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Data in Grav et al (2011) and Grav et al (2012) indicate the albedo distribution for the Trojans becomes much wider below ;30 km (approximately magnitude 11 for albedo value 0.07), but there is no statistically substantial difference between the L4 and L5 populations at these smaller sizes. Additionally, recent observations focused on Lucy mission targets (e.g., Buie et al 2018Buie et al , 2021Mottola et al 2023) found that WISE albedo determinations for Trojans could be systematically too high (an issue possibly related to the shape uncertainty).…”
Section: Bias-corrected L4/l5 Populationsmentioning
confidence: 99%
“…Data in Grav et al (2011) and Grav et al (2012) indicate the albedo distribution for the Trojans becomes much wider below ;30 km (approximately magnitude 11 for albedo value 0.07), but there is no statistically substantial difference between the L4 and L5 populations at these smaller sizes. Additionally, recent observations focused on Lucy mission targets (e.g., Buie et al 2018Buie et al , 2021Mottola et al 2023) found that WISE albedo determinations for Trojans could be systematically too high (an issue possibly related to the shape uncertainty).…”
Section: Bias-corrected L4/l5 Populationsmentioning
confidence: 99%
“…In this case this condition occurs because, due to its orbital inclination, the geocentric ecliptic latitude of Eurybates never exceeds ±10°. Keeney et al (2021), as a part of their program for the determination of size and shapes of the Lucy targets via stellar occultations (Buie et al 2021), have reported their preliminary results about a Eurybates event recorded on 2021 October 20.5 UT with nine usable chords. By projecting the shape models corresponding to our two solutions onto the plane of the sky at the time of the occultations and by overplotting the occultation chords, it was possible to unambiguously identify the correct pole solution, which is marked in Figure 5 with a red circle.…”
Section: Sidereal Period Pole and Shapementioning
confidence: 99%
“…Lucy is a NASA mission of the Discovery class that will perform a fly-by tour through both L4 and L5 Jupiter Trojan clouds (Levison et al 2021;Olkin et al 2021). This paper is the fourth of a series (Buie et al 2018(Buie et al , 2021Mottola et al 2020) devoted to characterizing the rotational state and the photometric properties and to deriving sizes and shape models of the Lucy targets from disk-integrated photometry and stellar occultation observations. Among the Lucy targets are (3548) Eurybates and (21900) Orus, both located in the L4 swarm, for which close encounters are planned in 2027 August and 2028 November, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For (21900) Orus and (3548) Eurybates, we took the visual albedos (0.075 and 0.052, respectively) reported in Grav et al (2012) as the values of the geometric albedo at 550 nm and scaled our observations accordingly. Similarly, we scaled the spectrum of (11351) Leucus to the visible albedo (0.037) reported in Buie et al (2021) at 550 nm. Using zero phase angle geometric albedos as the output of our Hapke models both simplified the calculations required to obtain a spectrum and allowed us to incorporate albedo into our compositional fits, a constraint that is particularly important to include for relatively featureless spectra such as those of the Trojans in the VNIR, as pointed out in Emery & Brown (2004).…”
Section: Hapke Modelingmentioning
confidence: 99%